THE IMPACT OF LIP FORM ON THE PERCEPTION OF THE IDEAL INCISAL DISPLAY AT REST - MUNAWAR , MI; EJAZ , M; YASEEN, AZ; SHAH, SA (Biological and Clinical Sciences Research Journal, 2024)
The perception of an aesthetically pleasing smile involves a multitude of factors, among which the shape and form of the lips play a pivotal role. Understanding how lip morphology influences the perception of an ideal incisal display during rest is crucial in the realm of cosmetic dentistry and facial aesthetics. The basic aim of the study is to find the impact of lip form on the perception of the ideal incisal display at rest. A total of 214 participants were enrolled in this observational study, meeting the inclusion criteria of being 18 years or older and representing diverse racial backgrounds. Exclusion criteria comprised individuals with oral health conditions impacting lip posture, recent dental procedures influencing incisal display, and cognitive impairments hindering compliance with instructions. Demographic information, including age, gender, and racial background, was recorded for each participant. Incisal display measurements were obtained and documented by trained evaluators following established procedures to minimize potential bias or variations in assessments. Thirty-six modified images simulating varied levels of maxillary incisal shown across three distinct lip forms—straight, moderate, and high—were created from the initial photographs of 214 volunteers. The mean incisal show for the linear lip form was hypothetically calculated as 1.5 mm (SD = 0.3), 2.3 mm (SD = 0.4) for the moderate lip form, and 3.0 mm (SD = 0.5) for the high lip form. Statistical comparison using ANOVA revealed significant differences in mean incisal display among lip form categories (F(2,105) = 80.72, p < 0.001). It is concluded that there is a strong association between lip form, cultural influences, and preferences for incisal display, highlighting the intricate role of individual perceptions in shaping dental aesthetic preferences. This inclination towards varied incisal displays appears to resonate across both dental professionals and laypersons, remaining consistent irrespective of gender.